Current status and prospects of traditional Chinese medicine combined with stem cell therapy for chronic kidney disease - Qian, Tianyang; He, Yining; Han, Chao; Yan, Ruxue; He, Weiming (Frontiers in Pharmacology, 2025)
Renal fibrosis is one of the main pathological features of chronic kidney disease (CKD), and its treatment has been a hot research topic. Recent studies have shown that stem cell therapy can repair renal pathological changes and slow the progression of CKD. In addition, a large number of experiments have confirmed that traditional Chinese medicine (TCM), especially Chinese medicine compound preparations, has the advantage of multitargeting interventions to improve renal fibrosis. Therefore, stem cell therapy combined with TCM is expected to provide new therapeutic ideas and measures to solve kidney problems. This article reviews the current status of TCM combined with stem cell therapy for CKD, discusses existing problems, and proposes future prospects.